In Search of a Professional Identity - CHAUHAN, SONIKA (THE PRIMARY TEACHER, 2015)
Teaching is one of the most arduous and demanding professions. Many teachers enter the profession brimming with ideas with the aim to inspire young students and to realise their potentials. What makes teaching particularly challenging is the diverse nature of classrooms and the expectation that every child will be brought into the fold of learning. Diverse classrooms often demand that teachers play varied roles ranging from a counsellor, storyteller, actor, writer, orator and many others. Despite this many teachers enjoy the complexities of their work. Teaching in a primary school for the past several years, has been the most rewarding and satisfying experience I have had. I have enjoyed every aspect of my work: selecting and designing subject content, developing exciting ways of engaging students with new and complex concepts and issues, reaching out to quieter and disinterested children, telling them animated stories about the worlds of fantasy and reality and making sure they learn.